INTERACTIVE INSTALLATION AND PORTUGUESE FEMINISTS - Sílvia Barros Pinto; Nelson Zagalo (Conhecimento Online, 2024)
The Checkers Game installation wanted to create a space for reflection on issues that focused on the violation of human rights, particularly the violation of women's rights. For the development of the project, the reality to be contemplated was delimited and, in this sense, an illustration of the framework of feminism in the Portuguese context of the late 19th and 20th centuries was drawn up. The installation interface, which merged the real world with the virtual world, since the tangible component of the installation platform consists of a cube and four game pieces and it is combined with a digital component, that consists of two projections associated with the sound element that prevail during the performance. This interactive installation assumes the participation of two participants who interact with each other and a computer system, that truck the participants movements activating a set of choices and actions and/or images corresponding to a previously established narrative sequence. This sensory component is achieved using a computer vision system. The computer applications implemented use the Processing language together with the OPENCV, Serial and ESS libraries. This empirical study employed a multimethodological framework known as the Development Methodology. The adopted methodology consisted of carrying out four interaction sessions, followed by the completion of an interaction assessment questionnaire.